Danskernes smag for litteratur - Hjarvard, Stig (Passage - Tidsskrift for litteratur og kritik, 2017)
Stig Hjarvard: “The Danes’ Taste for Literature” On the basis of a nationwide survey among book readers in Denmark it is demonstrated how literary taste preferences and reading behavior are related to social and cultural divisions as well as demographic differences in terms of age and gender. A model of two types of reading is developed to consider the appreciations implicated in the reading of fiction. A majority of Danish readers has a preference for an experiencing type of reading while a minority prefers a more distant and evaluative type of reading.